A case of hybrid verrucous carcinoma with lymph node metastasis: A rare case report (Indian Journal of Case Reports, 2020)
Verrucous carcinoma (VC) constitutes around 2–16% of total oral carcinomas. It tends to recur; however, lymph node metastasis is a rare finding. There are around 20% of VC cases associated with dysplasia/minimal invasion. Different names were used by many authors for those in-between varieties of VC. The clinical data, biological behavior, and histopathological features for that in-between variety of VC are not clearly defined. The previous case reports of VC with lymph node metastasis were attributed to the presence of dysplasia/minimal invasive component, along with pure VC. In this case report, we discuss pure VC and in-between varieties of VC. A universal name should be used for those lesions and should be incorporated in the World Health Organization classification. Careful examination of VC biopsy is mandatory to rule out any focal area of dysplasia/microinvasion as they suggest the probability of nodal metastasis.